The NO-donor MPC-1011 stimulates angiogenesis and arteriogenesis and improves hindlimb ischemia via a cGMP-dependent pathway involving VEGF and SDF-1α. (July 2020) - Gomes de Almeida Schirmer, Brigida; Crucet, Margot; Stivala, Simona; Vucicevic, Goran; da Silva Barcelos, Luciola; Vanhoutte, Paul M.; Pellegrini, Giovanni; Camici, Giovanni G.; Seebeck, Petra; Pfundstein, Svende; Stein, Sokrates; Paneni, Francesco; et al.
Abstract: Background and aims: Peripheral arterial disease (PAD) is an important cause of morbidity and mortality with little effective medical treatment currently available. Nitric oxide (NO) is crucially involved in organ perfusion, tissue protection and angiogenesis. Methods: We hypothesized that a novel NO-donor, MPC-1011, might elicit vasodilation, angiogenesis and arteriogenesis and in turn improve limb perfusion, in a hindlimb ischemia model. Hindlimb ischemia was induced by femoral artery ligation in Sprague-Dawley rats, which were randomized to receive either placebo, MPC-1011, cilostazol or both, up to 28 days. Limb blood flow was assessed by laser Doppler imaging. Results: After femoral artery occlusion, limb perfusion in rats receiving MPC-1011 alone or in combination with cilostazol was increased throughout the treatment regimen. Capillary density and the number of arterioles was increased only with MPC-1011. MPC-1011 improved vascular remodeling by increasing luminal diameter in the ischemic limb. Moreover, MPC-1011 stimulated the release of proangiogenic cytokines, including VEGF, SDF1α and increased tissue cGMP levels, reduced platelet activation and aggregation, potentiated proliferation and migration of endothelial cells which was blunted in the presence of soluble guanylyl cyclase inhibitor LY83583. In MPC-1011-treated rats, Lin − /CD31 + /CXCR4 + cells were increased by 92.0% and Lin − /VEGFR2 + /CXCR4 + cells by 76.8% as compared to placebo. Conclusions: Here we show that the NO donor, MPC-1011, is a specific promoter of angiogenesis and arteriogenesis in a hindlimb ischemia model in an NO-cGMP-VEGF- dependent manner. This sets the basis to evaluate and confirm the efficacy of such therapy in a clinical setting in patients with PAD and impaired limb perfusion. Graphical abstract: Image 1 Highlights: PAD is a debilitating disease caused by abnormal narrowing of arteries with little or no medical treatment options existing. Novel and unique NO donor, MPC-1011, promotes angiogenesis via NO-mediated signaling and proliferation of endothelial cells. Thus, MPC-1011 might be successfully used in clinical setting in patients with PAD or in those with impaired limb perfusion.